Prevention Fraud Pengelolaan Dana BUMDes dengan Sistem Pengendalian Internal sebagai Moderasi - Safrizal Safrizal (Politeknik Negeri Bengkalis, 2022)
This study aims to determine the factors that influence the prevention of fraud by using a competency variable moderated by an internal control system. This quantitative research was conducted in a sub-district in one of the Meranti Islands Regency, Riau. The research population was 12 BUMDes with a saturated sample technique (survey) which involved respondents as informants on the research questionnaire. The results of the study show that competence has an effect on fraud prevention, meanwhile through moderating regression analysis, it shows that the internal control system is not able to moderate competence in fraud prevention.Â Keywords: prevention fraud, competency, internal control system